Analisis Kesulitan Soal Pemecahan Masalah Pada Buku Sekolah Elektronik (BSE) Pelajaran Matematika Kurikulum 2013 revisi 2017 - Yulia Rahayu; Ali Umar; Rosliana Harapan (Jurnal Basicedu, 2021)
This study aims to analyze and describe the level of difficulty of solving mathematical problems in terms of the components of the problem: type of problem, type of number, type of operation, many operations, many questions, sufficiency of data, and similarity with previous questions and difficulty level of problem solving questions in the Electronic School Book (BSE) Mathematics for Senior High School (SMA) class X 2013 curriculum revision of 2017. This research uses literature review or literature study with a descriptive qualitative approach. Data collection methods used were the determination of mathematics teaching materials/textbooks; determination of problem-solving items contained in the competency test. The data analysis technique uses the stages of data reduction, data presentation, and conclusion. The results showed: 1) There are 18% problem solving questions or 20 questions out of 109 total questions; 2) Type of problem solving 55% routine and 45% nonroutine; 2) the dominant number type of whole number is 60%; 3) More types of operations use multiplication operations as much as 90%; 4) Many dominant operations use more than one operation as much as 100%; 5) Many dominant questions use one question as much as 70%; 6) Has sufficient complete data as much as 75%; 7) As many as 60% of the questions were not similar to the previous questions. So that the problem solving questions in the School Electronic Book (BSE) class X SMA are categorized as having an Easy difficulty level.